Composite materials made of waste tires and polyurethane resin: A case study of flexible tiles successfully applied in industry (2021)
ABSTRACT: This research presents a case study of producing flexible tiles from rubber powders obtained from automobile tire waste using a polyurethane resin as a binder matrix. The process was made in collaboration with a company located in Colombia, where the manufacturing of these materials has been optimized. The material is a green solution to an increasing worldwide problem, rubber car tires mostly put in landfills or burned to extract their reinforced steel wires instead of properly recycled. Several rubber contents and particle size distributions were investigated and tested. Tension, density, scanning electron microscopy, and thermo-gravimetric analysis characterization were used to evaluate the composites. Leaching analysis of contaminant are also included. Results shows that the amount of rubber used is quite large in comparison with the binder, maximizing the rubber in the formulations, and thus using more waste. The flexible characteristics of both resin and rubber enable these composites to be used in multiple applications. The tensile tests showed the composite can work very well for structural applications of low solicitations, such as wall covers, soft floors and barriers. The project is a successful example of a small-medium enterprise company that contributes to the circular economy of these highly pollutant materials.